2020
DOI: 10.1172/jci.insight.139983
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric folding correction of F508del and rare CFTR mutants by elexacaftor-tezacaftor-ivacaftor (Trikafta) combination

Abstract: Based on its clinical benefits, Trikafta — the combination of folding correctors VX-661 (tezacaftor), VX-445 (elexacaftor), and the gating potentiator VX-770 (ivacaftor) — was FDA approved for treatment of patients with cystic fibrosis (CF) carrying deletion of phenylalanine at position 508 (F508del) of the CF transmembrane conductance regulator ( CFTR ) on at least 1 allele. Neither the mechanism of action of VX-445 nor the susceptibility of rare CF folding mutants to Trikafta are known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
216
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(248 citation statements)
references
References 57 publications
18
216
0
Order By: Relevance
“…Lukacs and group have demonstrated that VX-661 and VX-809 are type I correctors that stabilize the MSD2-NBD1 interface, and other correctors stabilize NBD1 (type III) or NBD2 (type II) [ 20 , 37 ]. VX-445 synergistically rescues F508del-CFTR folding with type I and II correctors but not with a type III corrector, suggesting that it may be a class III corrector that stabilizes NBD1 [ 38 ], which may not be as advantageous in the c.3700A>G NBD2 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Lukacs and group have demonstrated that VX-661 and VX-809 are type I correctors that stabilize the MSD2-NBD1 interface, and other correctors stabilize NBD1 (type III) or NBD2 (type II) [ 20 , 37 ]. VX-445 synergistically rescues F508del-CFTR folding with type I and II correctors but not with a type III corrector, suggesting that it may be a class III corrector that stabilizes NBD1 [ 38 ], which may not be as advantageous in the c.3700A>G NBD2 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Class-II modulators appear to act synergistically with Class I modulators restore assembly of F508del-NBD1 with CL4 in MSD2 of CFTR. (Rosser, Grove et al 2008, Grove, Rosser et al 2009, Ren, Grove et al 2013, Veit, Roldan et al 2020). Modulators act on arrested intermediates of CFTR but cannot rescue the function of off-pathway and misfolded conformers of CFTR mutants {Van Goor, 2014 #8219}.…”
Section: Resultsmentioning
confidence: 99%
“…The Class I modulator VX-809 does increase the accumulation of N1303K-CFTR, but not proper folding. Treatment with VX-809 alone, or in combination with the tool compounds in the Class II modulator family, or VX-441, which is used in combination with Class I modulators clinically, does not restore N1303K-CFTR function in heterozygous or homozygous native human airways cells from CF patients (Veit, Roldan et al 2020). However, we were able to fix the folding of a small fraction of N1303K-CFTR in cells that are cultured at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has already led to the development of four compounds that are currently on the market: lumacaftor (VX809), ivacaftor (VX770), tezacaftor (VX661), elexacaftor (VX445) and their combinations [10], among which the recently approved Trikafta [11,12].…”
Section: Introductionmentioning
confidence: 99%